2021
DOI: 10.3329/bjms.v20i2.51561
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Prevention of Metabolic Syndrome and Cardiovascular Diseases

Abstract: Objective: About 90% of cardiovascular diseases can be prevented. In recent years, the role of vitamin D in the prevention of cardiovascular disease and components of metabolic syndrome has been actively discussed. The study aimed to investigate the possible influence of vitamin D3 on the emergence risk of metabolic syndrome and adverse cardiovascular events. Materials and methods: The study enrolled a total of 336 people (170 males and 166 females) aged 50-60 years. For comparative analysis, two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…After reviewing 5,089 studies obtained from the databases and 16 additional records identified through other meta-analyses, 5,081 studies were excluded, and 24 RCTs were included in the final analysis ( 22 25 , 27 , 32 50 ). Figure 1 shows the selection procedures and results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing 5,089 studies obtained from the databases and 16 additional records identified through other meta-analyses, 5,081 studies were excluded, and 24 RCTs were included in the final analysis ( 22 25 , 27 , 32 50 ). Figure 1 shows the selection procedures and results.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the selection procedures and results. In total, twenty-two studies reported a definitive stroke outcome in published reports ( 22 25 , 27 , 32 , 34 42 , 44 50 ). The authors of two studies provided supplementary data on stroke ( 33 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A graphical representation with the weighted mean difference and its SE is also given for each study. References: Vitamin C ( [51], [56], [61], [85], [112]); Vitamin D ( [33], [34], [35], [42], [43], [44], [49], [50], [52], [57], [63], [64], [74], [75], [122], [79], [81], [83], [87], [97], [99], [100], [104], [105], [107], [108], [111], [113], [124]); Vitamin E ( [115], [117], [120], [86], [88], [89], [90]) The pooled mean difference is given in mm Hg with its 95% CI. The weighted mean difference in mm Hg and its 95% CI is given for each study.…”
Section: Systolic Blood Pressurementioning
confidence: 99%